PESANTREN AND ECONOMIC SUSTAINABILITY: A MAQASHID-BASED APPROACH AL-SYARI'AH - Moch. Faisal; Rasad Mulyadi; Abidin Nasyar; B. Syafuri; Apud (Cakrawala Pedagogik, 2025)
This study aims to examine the role of Islamic boarding schools (pesantren) in achieving economic sustainability through a Maqashid al-Shari’ah–based approach. Pesantren function not only as institutions for religious education but also as socio-economic entities with strategic potential to promote community empowerment and economic self-reliance. The Maqashid al-Shari’ah framework is employed as a normative foundation to analyze how pesantren-based economic activities can be oriented toward achieving public welfare (maslahah) and holistic well-being (falah).This research adopts a qualitative approach using a library research method by analyzing books and scholarly journal articles published from 2018 onward that are relevant to pesantren, economic sustainability, and Maqashid al-Shari’ah. The findings indicate that the implementation of maqashid principles particularly the protection of wealth (hifz al-mal), intellect (hifz al-‘aql), and life (hifz al-nafs) strengthens the economic sustainability of pesantren through ethical, just, and sustainable economic management. Moreover, the maqashid-based approach encourages transparent and accountable economic governance oriented toward community empowerment. This study concludes that pesantren have strong potential to serve as an alternative model of value-based sustainable economic development within the framework of Islamic economics, particularly in addressing contemporary economic challenges.